Klasifikasi Tipologi Zona Perwilayahan Wilayah Peri-Urban di Kecamatan Kartasura, Kabupaten Sukoharjo - Nela Agustin Kurnaianingsih (Jurnal Wilayah dan Lingkungan, 2013)
Pheri-Urban Zone comes as transition zone between rural and urban, have given something unique characteristic on region types. The growth makes pheri-urban zone have urban characteristic with high population density and heterogeneity of activities, and have rural characteristic with existence of agricultural sector. That does all arise as growth effect from urbancore. Kartasura Sub-District is one of pheri-urban zone, which arose as growth effect from Surakarta city on physic aspect, social aspect, and economic aspect. The growth of Surakarta city made some villages in Kartasura changed to urban ways. Beside of that, the growth of Kartasura Sub-District become urban area,was influenced by historical story, in long time ago Kartasura Sub-district was one of Islam Palace in Indonesia before was moved to Surakarta City. However, with no spread growth in Kartasura, could make existence of rural characteristic. For the proof, although in Kartasura occur land use change in agricultural sector, this sub-district had income increase in every year for this sector. Uniqueness of blend from urban ways and rural ways in Kartasura Sub-District made one research question, how is the classification of pheri-urban zone in Kartasura, absolutely is looked from physic, social and economic aspects? From that research question, this research was done to identification urbanization level for villages in Kartasura Sub-District into three pheri-urban zones: primary pheri-urban zone, secondary pheri-urban zone, and rural pheri-urban zone. This classification used spatial analysis with GIS. For the result, in Kartasura have three pheri-urban zones: 2 villages include primary pheri-urban zone with landmass is 265 Ha, 8 villages include secondary pheri-urban zone with landmass is 1.368 Ha and 2 villages include rural pheri-urban zone with landmass 290 Ha. from this research, was known some characteristic of pheri-urban zone in Kartasura, which can make different from the other pheri-urban zones.